(Un)covering Poland between PR and presidency. A quantitative content analysis of print news coverage of the Polish EU presidency in Flanders - Velders, Khaël; Joye, Stijn; Biltereyst, Daniël; Bonte, Thibault; Delcart, Eveline (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Cross-national and longitudinal comparative research on the media coverage of EU-related news has gained increasing interest and momentum, but is still rare and generally focuses on the EU as an intergovernmental institution, hence remaining largely ignorant of the particular flows of news in between the member states of the EU. The following analysis provides insight into the media coverage of the Polish EU presidency in the region of Flanders. For this quantitative content analysis, our scope is narrowed to three Flemish media sources. Based on a predetermined set of keywords related to the Polish case and using the newspaper search engine Mediargus, we collected 735 articles for analysis. In conclusion, the analyzed news sample devoted little attention to the Polish EU presidency. News items relevant to Poland’s presidency of the EU were concentrated around the presidential inauguration, limited in size, not necessarily political in nature, and favored objective news reporting with absence of a discernible attitude towards Poland.